Interpersonal Communication Skills in Shaping Academic Performance among University Students - Mishra, Ishita; Kumari, Pushpa (Indian Journal of Extension Education, 2025)
Excellent academic performers need good communicative students who must have the skill to represent their thoughts and ideas with clarity and confidence, whether verbally or non-verbally. It’s about upholding skills of transmitting knowledge and information systematically channeled through the presentation of written form, easy for others to understand. The study aimed to find out communication skills academically and their value in encompassing academic performance among students enrolled in undergraduate courses in various faculties of Banaras Hindu University, Varanasi, 2024. Responses were obtained from 111 total respondents, both boys and girls, based on the communication skill inventory. The data was collected using a closed-ended self-structured questionnaire using a simple random sampling technique. The results were analyzed using SPSS version 16, which showed levels of achievement from moderate to high levels of communication skills in listening, speaking, reading, and presentation skills. The result shows that the majority of the students agreed that their communication skill level falls at a moderate level.